PERBEDAAN POLA KONSUMSI IKAN DAN STATUS KESEHATAN GIGI DAN MULUT PADA ANAK USIA SEKOLAH DASAR (7-12 TH) DI DAERAH PESISIR DAN NON PESISIR KABUPATEN JEPARA TAHUN 2012 - Aprilia Fitriyanti; Aning Susilowati; Uswatun N.A. Darjono (Odonto : Dental Journal, 2014)
Background: Adolescents (7-12 years old) have a high potential of caries and periodontal infections. It happens due to fish diet of children at coastal and non coastal region. Fish nutrient contains mineral, fluoride which prevents demineralisation process. In addition, there is fatty acid which contains anti inflammation that prevent periodontal disease. The aim of the study is to determine the difference between fish consumption habit and oral health of coastal and non coastal people at Jepara district in 2012. Method: This research used analysis observational method with cross sectional design. It was done in 50 children at coastal region and 50 children at non coastal region in 2012. Those samples were collected using convenience sampling method. The fish diet pattern was measured with questionnaire. Caries status was measured with DMF-T index and gingival health was measured using Loe and Silness' gingival index. Study result was analyzed with Mann-Whitney comparative test. Result: The analysis result showed that there was a significant difference of fish consumption pattern (p=0,000), DMF-T status (p=0,000) and gingival index (p=0,000) between people at coastal and non coastal area. Conclusion: There is a significant difference between fish consumption pattern and oral health status of coastal and non coastal children at Jepara district in 2012.